2017
DOI: 10.7150/jca.19566
|View full text |Cite
|
Sign up to set email alerts
|

Development of a new analog of SGK1 inhibitor and its evaluation as a therapeutic molecule of colorectal cancer

Abstract: Colorectal cancer (CRC) is one of the most leading causes of cancer-related death worldwide. The serum and glucocorticoid inducible kinase SGK1 is highly expressed and involved in several tumors. GSK650394, a SGK1 inhibitor, has been proved to be effective in impeding tumor growth in vitro. In this study, we developed a novel analog of GSK650394, and evaluated its effects on CRC cells and tumor growth both in vitro and in vivo. HCT116 cells were treated with a concentration gradient of new developed compounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…In colorectal cancer, transfection with a constitutively active SGK1 mutant significantly enhanced cell motility and cell migration via vinculin dephosphorylation ( 51 ). Liang et al ( 48 ) also found that SGK1 overexpression promoted colonic tumor cell migration, while SGK1 shRNA and inhibitors showed the inverse effects ( 72 ). In contrast, Lee et al ( 43 ) showed that SGK1 is upregulated in response to, and an important controller of, intestinal cell differentiation.…”
Section: Functional Roles Of Sgk1 In Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…In colorectal cancer, transfection with a constitutively active SGK1 mutant significantly enhanced cell motility and cell migration via vinculin dephosphorylation ( 51 ). Liang et al ( 48 ) also found that SGK1 overexpression promoted colonic tumor cell migration, while SGK1 shRNA and inhibitors showed the inverse effects ( 72 ). In contrast, Lee et al ( 43 ) showed that SGK1 is upregulated in response to, and an important controller of, intestinal cell differentiation.…”
Section: Functional Roles Of Sgk1 In Cancermentioning
confidence: 99%
“…We obtained similar results in PCa cells treated with GSK650394 ( 20 ), the first developed inhibitor of SGK ( 49 ). Recently, a new SGK1 inhibitor analog was developed, the GSK650394 analog QGY-5-114-A, which significantly inhibited CRC cell migration in vitro ( 72 ).…”
Section: Functional Roles Of Sgk1 In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…While combining mTOR with Akt inhibition showed promise with less toxicity, it seems that Akt inhibitor monotherapy had low clinical activity partly due to poor tolerability [322][323][324]. Pre-clinical studies on inhibition of SGK, another target of mTORC2, for the treatment of a variety of cancers are also showing promise [327,328,331]. SGK1 could play a role in enhancing uptake of unsaturated fatty acids in hypoxic lung cancer cell [327].…”
Section: Other Inhibitors Of the Mtor Pathwaymentioning
confidence: 99%
“…It has been previously reported that phosphorylation of the Focal Adhesion Kinase (FAK) led to the activation of Src/Syk/STAT3 and Akt, which are crucial signaling molecules involved in enhancing cell adhesion and protecting cells from drug-induced cell apoptosis [53]. Activating Integrin β1/FAK and its downstream Src-Syk-STAT3/Akt signaling pathway can promote enhanced cell adhesion and CAM-DR in MM cells [53, 54]. In this study, we have shown that overexpression of Numbl promoted the adhesion of myeloma cells to FN or HS-5 cells via activation of Integrin β1-FAK and the subsequent activation of Akt pathway, which eventually facilitated the survival and drug resistance of myeloma cells.…”
Section: Discussionmentioning
confidence: 99%